2015
DOI: 10.4236/ns.2015.76036
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 1246 Cases of Orbital Lesions: A Study of 17 Years

Abstract: Purpose: The aim of this study is to present an analysis of orbital lesions by classifying them according to the site of origin in patients of all ages presenting at a tertiary care eye hospital from 1996 till 2012. Methods: 1637 patients were initially enrolled in this descriptive case series. Clinical data of 1246 patients who completed the study during 17 years were analyzed. Orbital lesions of the patients were examined and managed medically or surgically as per requirement. The histopathological reports o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…This was similar to the study by Balogun et al one of the peak age groups was 20 This was however different from the findings by Anunobi et al [2] with 51.1% of cases b children under 15 years old and those of Bekibele [3] in Ibadan, Nigeria with 50% of children and young adults from 0 to 20 years old. It was also at variance with the findings of Asad Aslam Khan et al [4] who predominance of adults with 57.47% of cases in Age distribution of oculoplastic disorders group in our study was 21-30 years and followed by 31 to 40 years. This was similar to the study by Balogun et al [1] where one of the peak age groups was 20-29 years.…”
Section: Fig 2 Age Distribution Of Oculoplastic Disorderssupporting
confidence: 76%
See 1 more Smart Citation
“…This was similar to the study by Balogun et al one of the peak age groups was 20 This was however different from the findings by Anunobi et al [2] with 51.1% of cases b children under 15 years old and those of Bekibele [3] in Ibadan, Nigeria with 50% of children and young adults from 0 to 20 years old. It was also at variance with the findings of Asad Aslam Khan et al [4] who predominance of adults with 57.47% of cases in Age distribution of oculoplastic disorders group in our study was 21-30 years and followed by 31 to 40 years. This was similar to the study by Balogun et al [1] where one of the peak age groups was 20-29 years.…”
Section: Fig 2 Age Distribution Of Oculoplastic Disorderssupporting
confidence: 76%
“…In a similar study by Bekibele et al in Ibadan Nigeria, 50% of cases were children and young adults from 0 to 20 years old [3]. However in a study in Pakistan, Asad Aslam Khan et al observed a predominance of adults with 57.47% of cases [4] while Balogun etal had two peak age groups of 0-9 years (22.7%) and 20-29 years (19.3%) [1].…”
Section: Introductionmentioning
confidence: 93%
“…Procedures that can be performed will range from simple biopsy to near total or total resection depending on the histological variant. 3,4,5 Most appropriate surgical approach chosen for making complete excision possible. Approaches can be divided into transorbital and extra-orbital approaches.…”
Section: Discussionmentioning
confidence: 99%
“…1 These tumours include tumours of lacrimal gland, adipose tissue, fibrous tissue, muscle tissue, bone and cartilage, tumours of blood vessels and lymphatics, tumours of peripheral nerves and cranial nerves, tumours of optic nerve, tumours of dural meninges, arachnoid and metastasis from adjacent or distant site. 1,2,3,4 Orbital tumours present with visual disturbances as decreased vision and double vision, proptosis, periorbital and retro-orbital pain, lacrimation, conjunctival oedema and inflammation. 3,4 Many neoplastic conditions masquerade as or mimic other less aggressive inflammatory conditions and should be differentiated before definitive therapy is planned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation